Campaign-style enforcement and corporate environmental governance: evidence from China’s central environmental inspection - Dong, Yukai; Huang, Junrong; Li, Yuhong (Frontiers in Public Health, 2025)
Campaign-style enforcement is a crucial approach to bridging enforcement gaps and improving environmental quality. Existing literature has largely focused on its impacts on environmental performance, government actions, and public response, while relatively neglecting its effects on enterprises. Using a staggered difference-in-differences (DID) approach and data from China’s Central Environmental Inspection (CEI), this study examines the impact and mechanisms of campaign-style enforcement on corporate environmental governance, as well as the moderating role of government–business relations. Results show that campaign-style enforcement can lead heavily polluting enterprises to increase their environmental investments, though this effect is weakened when government–business relations are close. Furthermore, under the pressure of the CEI, local governments primarily employ punitive measures rather than financial incentives to prompt these enterprises to increase their environmental investments. Heterogeneity analysis reveals that campaign-style enforcement has a more pronounced effect on small firms and firms located in eastern regions. These results highlight regional differences in enforcement effectiveness and enrich understanding of how campaign-style environmental enforcement shapes corporate behavior, offering valuable insights for future CEI policies.